American Academy of Otolaryngology—Head and Neck Foundation Clinical Practice Guideline: Tinnitus. (2nd September 2014) - Tunkel, David E.; Bauer, Carol A.; Sun, Gordon H.; Rosenfeld, Richard M.
Abstract : Program Description: More than 50 million people in the United States have reported experiencing tinnitus, an estimated prevalence of 10% to 15% in adults. The multidisciplinary American Academy of Otolaryngology—Head and Neck Foundation–developed "Clinical Practice Guideline: Tinnitus, " will be presented. This guideline provides evidence‐based recommendations for clinicians managing patients with tinnitus. The guideline discusses evaluation of patients with tinnitus, including selection and timing of diagnostic testing and specialty referral to identify underlying treatable pathology. It then focuses on the evaluation and treatment of patients with persistent primary tinnitus, with recommendations to evaluate and measure its impact, for determining the most appropriate interventions to improve symptoms and quality of life for tinnitus sufferers. Educational Objectives: (1) Practice accurate and efficient diagnosis of primary tinnitus. (2) Improve the quality of care and mitigate the personal and social impact of persistent, bothersome tinnitus.